REVOLUÇÃO DOS CRAVOS. IMAGEM E MITOLOGIA - JORGE, Lidia (Studia Universitatis Babeș-Bolyai Philologia, 2019)
The Carnation Revolution. Image and Mythology. Eduardo Gageiro’s photograph showing a soldier about to take the portrait of dictator Salazar off the wall at the political police headquarters the day after the Portuguese Revolution of April 25, 1974 evokes a major and symbolic turn in the overthrow of the regime and works as an allegory of change. Yet after all these years, the outcome of that revolutionary dream spurred on by utopian desire remains complex, and its realisation in the form of democracy conceals the loss of lustre of the initial dream. In the light of this apparent contradiction, it is worth revisiting the circumstances that galvanized the revolution and the benefits obtained in terms of rights and freedom, as illustrated by Literature. Fiction, in particular, amplifies History by its storytelling of myths in a space where human desire takes on a role of reconstructing invisible realities. It is in this context that the book entitled Les mémorables (The Outstanding) finds its place. REZUMAT. Revoluția garoafelor. Imagine și mitologie. Fotografia lui Eduardo Gageiro reprezentând un soldat pe punctul de a da jos portretul dictatorului Salazar de pe peretele sediului poliției politice la o zi după Revoluția Portugheză din 25 aprilie 1974 evocă o turnură majoră și simbolică în răsturnarea regimului și funcționează ca alegorie a schimbării. Însă, după atâția ani, bilanțul visului revoluționar încurajat de dorințe utopice rămâne unul complex, iar concretizarea lui ca democrație ascunde pierderea strălucirii visului inițial. În lumina acestei aparente contradicții, merită să revenim asupra condițiilor ce au influențat revoluția și asupra câștigurilor obținute sub forma drepturilor și a libertății, așa cum o evocă Literatura. Ficțiunea, în special, amplifică Istoria prin povestirea miturilor, într-un spațiu unde dorința umană preia rolul de reconstrucție a realităților invizibile. În acest plan se înscrie volumul ce poartă titlul Les mémorables (Neuitații). Cuvinte cheie: revoluție, garoafe, mit, utopie, istorie, neuitați.